Effects of the corrosion of main bar and stirrups on the bond behavior of reinforcing steel bar. (20th November 2019) - Lin, Hongwei; Zhao, Yuxi; Yang, Jia-Qi; Feng, Peng; Ozbolt, Josko; Ye, Hailong
Highlights: Serious corrosion of stirrups can result in wider longitudinal crack width. Serious corrosion of stirrups can exacerbate the deterioration of bond strength. A bond-slip model considering the corrosion of main bar and stirrups is proposed. Abstract: Pull-out tests have been carried out to study the combined effects of corrosion of main bar and stirrups on the bond behavior. The main experimental variables included concrete cover thickness, stirrup spacing, and corrosion levels of main bar and stirrups. It was found that the corrosion of stirrups could lead to serious cover cracking and the way of stirrup corrosion influencing the cover cracking patterns was affected by the stirrup spacing. Moreover, the test results showed that the propagation of transverse cracks was similar to that of longitudinal cracks. In comparison to the case that merely main bar was corroded, the coupled corrosion of main bar and stirrups exacerbated bond deterioration. It was also found that the frictional bond stress was negatively affected by the corrosion of stirrups. Based on the experimental results and previous studies, a bond stress-slip model for RC with corroded main bar and corroded stirrups was for the first time proposed. The effectiveness of the proposed bond-slip model was finally validated by FE modelling.